Characterization of Stearic Acid and Paraffin Incorporated with Aluminium as Filer for the Development of Phase Change Material Composite in Thermal Energy Storage - Sumaiya, Zainal Abidin; S. A. A., Ghani; Uyi Osazuwa, Osarieme; Saidatul Shima, Jamari (IOP Publishing, 2020)
With the increasing energy demand, shortage of energy has drawn attention towards the utilization of non-renewable energy sources. The development of thermal energy storage (TES) to fulfil the energy demand that has increased progressively over time is of great interest. TES systems are widely employed industrially especially for phase change materials (PCM) used in many fields with several applications. This study aims to synthesize, characterize and study the physicochemical and thermal properties of stearic acid and paraffin incorporated with aluminium as filler for the development of PCM composite. The PCM composites were prepared using 80wt% for the Al/SA and 80wt% Al/paraffin, respectively. The PCM composites were characterized using thermal gravimetric analysis, differential scanning calorimetry and scanning electron microscopy. Results showed good compatibility in physicochemical properties between stearic acid (SA), paraffin and aluminium (Al), respectively. It was observed that the thermal stability studied using thermal gravimetric analysis revealed slightly better stability exhibited by the paraffin PCM composite. This was as a result of the steeper slope exhibited by the stearic acid TGA curve as against that of the paraffin curve. Also, density analysis has resulted in an increment for both composite materials whereas; aluminium incorporated in paraffin composite has shown higher increment of density as compared with stearic acid composite. Therefore, PCM composite made from paraffin will be more effective as a TES material when used industrially as compared to the stearic acid PCM composite.